2012
DOI: 10.5402/2012/946019
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Malignant Fibrous Histiocytoma Associated with Leukemoid Reaction or Leukocytosis: A Comprehensive Review

Abstract: Inflammatory malignant fibrous histiocytoma (IMFH) associated with leukemoid reaction (LR)/leukocytosis is a rare entity. In this paper, we search PubMed for all known cases of IMFH associated with LR/leukocytosis in an attempt to draw conclusions about this variant's response to treatments and its pathophysiology. Medline electronic database was searched using key words such as malignant fibrous histiocytoma, leukemoid reaction, and leukocytosis. A total of 16 patients were found, twelve males (75%) and 4 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The current case could be further classified as immune-high (D and E), and/or highly vascularized (C) groups. Rapid growth and early metastasis have been observed in IUPS, and the involvement of G-CSF, IL-6, IL-7, IL-8, SCF, TGB, and G-CSF have also been suggested [ 4 , 14 , 15 ]. IL-6 is an important cytokine that plays various roles in many cells, such as proliferation of T lymphocytes, induction of B lymphocyte maturation, promotion of the growth of erythroid cells, myeloid cells, and megakaryocytes, and the induction of acute phase protein production by hepatocytes [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current case could be further classified as immune-high (D and E), and/or highly vascularized (C) groups. Rapid growth and early metastasis have been observed in IUPS, and the involvement of G-CSF, IL-6, IL-7, IL-8, SCF, TGB, and G-CSF have also been suggested [ 4 , 14 , 15 ]. IL-6 is an important cytokine that plays various roles in many cells, such as proliferation of T lymphocytes, induction of B lymphocyte maturation, promotion of the growth of erythroid cells, myeloid cells, and megakaryocytes, and the induction of acute phase protein production by hepatocytes [ 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many still favor its use, especially in cases with the highest risk of recurrence, given the potential of radiotherapy to decrease local recurrence . Following surgical resection, a recurrent leukocytosis frequently marks disease recurrence . The leukocytosis associated with these masses led some to initially believe that they were of lymphomatous origin, but they are now considered a subtype of dedifferentiated liposarcoma based on immunohistochemical and genomic analysis …”
Section: Discussionmentioning
confidence: 99%
“…Despite stimulating bone marrow to sustain leukocytosis, IL-3, GM-CSF, and G-CSF have been shown to stimulate the growth of clonogenic cells of some nonhematopoietic malignant cell lines in vitro [ 5 ]. Hurtado et al found that when G-CSF was overproduced by tumor cells, it had a tendency to encourage the development of myeloid-derived suppressor cells (MDSC), which could travel to lymph nodes to prevent dendritic cell-primed T lymphocytes from eliminating tumor cells [ 10 ]. Therefore, consistent with the clinical presentation of our case, paraneoplastic granulocytosis is often associated with rapid tumor growth and poor clinical prognosis, although it resolves with the treatment of the underlying cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In a comprehensive review of inflammatory malignant fibrous histiocytoma (IMFH) associated with LR or leukocytosis, the severity of LR was correlated with the time of death. Once the WBC reached 100*10 9 /L, the patients were not capable of tolerating any chemoradiation secondary to their unstable clinical condition [ 10 ]. Mabuchi also concluded that pretreatment leukocytosis was an independent prognostic factor in patients with cervical cancer [ 18 ].…”
Section: Discussionmentioning
confidence: 99%